2015
DOI: 10.5267/j.esm.2015.1.001
|View full text |Cite
|
Sign up to set email alerts
|

The microstructure and mechanical behavior of modern high temperature alloys

Abstract: Over the past decades, high entropy alloys (HEAs) have attracted continuously increasing research efforts because of their technological promise for structural applications and their scientific interest as a multi-component alloy exhibiting an overall random solid solution structure with high mixing entropy at high temperature. In this summary, we briefly review the recent studies focused on the structure and mechanical behavior of HEAs, covering the important issues from phase stability to elastic modulus, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 76 publications
1
4
0
1
Order By: Relevance
“…It also could be found that at a higher temperature, the curve showed more violent fluctuations, which was caused by the vibration of atoms and fading of the bonding strength between atoms. This phenomenon was also found in the experiments [13,40]. The nanoindentation load-displacement curves of HEAs with different Cu concentrations were shown in Figure 3(b).…”
Section: Resultssupporting
confidence: 81%
“…It also could be found that at a higher temperature, the curve showed more violent fluctuations, which was caused by the vibration of atoms and fading of the bonding strength between atoms. This phenomenon was also found in the experiments [13,40]. The nanoindentation load-displacement curves of HEAs with different Cu concentrations were shown in Figure 3(b).…”
Section: Resultssupporting
confidence: 81%
“…1, and a number of reviews of the HEA literature have been made over the past 5 years. 5,6,8,[10][11][12][13] These have been in the form of comprehensive and detailed summaries, such as the review by Zhang et al, 14 as well as shorter critical assessments, such as the recent work of Miracle. 15 However, none of these have critically assessed the evidence for the four core effects described above -this is one, and the most important, of the three key aims of this review, and is tackled to begin with.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoelectric properties can be tuned with respect to valence electron concentration (VEC) and a dimensionless thermoelectric figure of merit ( ZT ) of 0.012 at 505 °C was reached for Al 2 CoCrFeNi. The phase evolution of HEAs has been extensively studied both ex situ and in situ [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%